1995
DOI: 10.1080/14486563.1995.10648312
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Financial Benefits of Tourism in Major Protected Areas

Abstract: Tourism has emerged as an important economic activity in Australia. Australia's protected natural environment areas are amongst the nation's major tourist attractions. This article presents new estimates of the considerable financial value of tourism in five of Australia's World Heritage Areas (WHA.s ). An economic interpretation of the management objectives for protected areas has been developed to illustrate the nature of the problem of maximising the combined benefits of all uses, including conservation, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…It has been found that National park managers, such as those of the Queensland Parks and Wildlife Service, are constantly searching for reliable and efficient methods toestimate the economic impact oftheir national parks. Their investigations have focused upon tourism recreation values due to the ease of data collection (Driml and Common 1995;Pearson et al 2000). The hedonic price method is a relatively straightforward approach to measuring the recreational and aesthetic values that the local residents place on having a park.…”
Section: Discussion and Recommendations For The Use Of Hedonic Methodsmentioning
confidence: 99%
“…It has been found that National park managers, such as those of the Queensland Parks and Wildlife Service, are constantly searching for reliable and efficient methods toestimate the economic impact oftheir national parks. Their investigations have focused upon tourism recreation values due to the ease of data collection (Driml and Common 1995;Pearson et al 2000). The hedonic price method is a relatively straightforward approach to measuring the recreational and aesthetic values that the local residents place on having a park.…”
Section: Discussion and Recommendations For The Use Of Hedonic Methodsmentioning
confidence: 99%
“…Carlsen & Wood, 2004;Driml & Common, 1995;Kalter & Lord, 1968;KPMG, 2000;Leeworthy & Wiley, 2002;Lindberg & Denstadli, 2004;Stynes et al, 2002;Tremblay & Carson, 2007). Along with various monographic surveys, efforts have been made to develop generic methodologies (Stynes & Propst, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The economic significance of tourism in these forests needs to receive greater recognition. In the Wet Tropics of Queensland WHA further north, the changeover from logging to tourism yielded a seven-fold increase in revenue (Driml and Common 1995), and a similar result is likely if the central eastern rainforests made the same change (Ward 2000). The increase in tourism in State forests has received some political recognition to date, with the transfer of some State forest areas in northern NSW to the national parks estate.…”
Section: Tourism In Public Forestsmentioning
confidence: 97%